Accounting for social responsibility and its role in improving the quality of banking services A field study in a sample of commercial banks in Sulaymaniyah Governorate and Karmian Administration - Rzgar Ali Ahmed; Ali Omar Mohammed; Peshkawt Abdullah Abdul Karim (The Scientific Journal of Cihan University– Sulaimaniya, 2018)
Social responsibility in banks is considered to be the most recent stage of accounting development. This modern development was created as a result of the single increase in the size and decisions of banks that have wide financial, economic and social effects, which led to attention to the intellectual accounting framework of banks. Problems facing the accountant such as cost measurement and social return The main question of the problem is the role of social responsibility, which helps to provide information to improve the quality of banking services to the parties concerned to ensure a comprehensive evaluation process by society and the state's social performance level achieved by banks it is therefore necessary to integrate the social and environmental dimension into the strategy of these financial institutions to ensure their contribution to supporting environmental policies and improving environmental performance, and the formation of economic institutions that participate in the national economy. The term social and environmental responsibility is used to express the commitments of financial and banking institutions Goals for the benefit of society.